THERMOKINETICS OF WATER ADSORPTION IN ZEOLITE AGZSM-5 - Abdulxayev, Tolibjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Annotation. This article presents the thermokinetics of water adsorption in AgZSM-5 zeolite at a temperature of 303 K. To measure the adsorption thermokinetics, we used a system consisting of a universal high-vacuum adsorption setup and a differential modified microcalorimeter of the Tiana-Calve DAK-1-1A type connected to it. A correlation between the adsorption-thermokinetic characteristics was found and the molecular mechanism of water adsorption in the AgZSM-5 zeolite was revealed in the entire filling area. According to the thermokinetics, it was found that the Ag+ cations are located in screened positions of the ZSM-5 zeolite crystal lattice. The adsorption of a water molecule leads to the migration of Ag+ cations from the zeolite lattice into crosshairs formed by the intersection of straight and zigzag channels and the formation of ion/molecular complexes of various multiplicity in them. From the values of adsorption thermokinetics, it was established that polar water molecules with silver cations in zeolite form a nano-ion-molecular complex in the first coordination sphere.